Prediction of Quality of Life and Survival After Surgery for Symptomatic Spinal Metastases: A Multicenter Cohort Study to Determine Suitability for Surgical Treatment. Issue 5 (22nd July 2015) - Choi, David; Fox, Zoe; Albert, Todd; Arts, Mark; Balabaud, Laurent; Bunger, Cody; Buchowski, Jacob M.; Coppes, Maarten H.; Depreitere, Bart; Fehlings, Michael G.; Harrop, James; Kawahara, Norio; et al.
Abstract: BACKGROUND: Surgery for symptomatic spinal metastases aims to improve quality of life, pain, function, and stability. Complications in the postoperative period are not uncommon; therefore, it is important to select appropriate patients who are likely to benefit the greatest from surgery. Previous studies have focused on predicting survival rather than quality of life after surgery. OBJECTIVE: To determine preoperative patient characteristics that predict postoperative quality of life and survival in patients who undergo surgery for spinal metastases. METHODS: In a prospective cohort study of 922 patients with spinal metastases who underwent surgery, we performed preoperative and postoperative assessment of EuroQol EQ-5D quality of life, visual analog score for pain, Karnofsky physical functioning score, complication rates, and survival. RESULTS: The primary tumor type, number of spinal metastases, and presence of visceral metastases were independent predictors of survival. Predictors of quality of life after surgery included preoperative EQ-5D ( P = .002), Frankel score ( P < .001), and Karnofsky Performance Status ( P < .001). CONCLUSION: Data from the largest prospective surgical series of patients with symptomatic spinal metastases revealed that tumor type, the number of spinal metastases, and the presence of visceral metastases are the most useful predictors of survival and that quality of life is best predicted by preoperative Karnofsky, Frankel, and EQ-5D scores. The Karnofsky score predicts quality of life and survival and is easy to determine at the bedside, unlike the EQ-5D index. Karnofsky score, tumor type, and spinal and visceral metastases should be considered the 4 most important prognostic variables that influence patient management.